Discomfort glare and time of day - Kent, Michael G.; Altomonte, Sergio; Tregenza, Peter R.; Wilson, Robin (SAGE Publications, 2014)
There are strong reasons to suspect that glare sensation varies with time of the day. This study was designed to test whether such a relationship exists. Thirty subjects were exposed to an artificial lighting source at four times of the day. The source luminance was progressively increased and subjects were required to give Glare Sensation Votes (GSVs) corresponding to the level of visual discomfort experienced. Glare indices were calculated for every reported GSV, and results were statistically analysed. The findings indicated a tendency towards greater tolerance to luminance increases in artificial lighting as the day progresses. This trend was found not to be statistically related to the possible confounding variable of learning, providing evidence of an effect of time of the day on glare sensation.